Perceptions of Career Counselling Services among Undergraduate Students - Edris, Aden; Nor Mazlina, Ghazali; Azzahrah, Anuar; Amat, S.; Mahmud, M. I. (International Journal of Innovation, Creativity and Change (IJICC), 2019)
Career counselling services are essential to increase the employability of university graduates. This study aimed to explore the perceptions of university students to the career counselling practices at public universities. Two males and four females were involved in this study. Their involvement was on a voluntary-basis. The data were collected using a semi-structured interview method and analysed using NVivo 12 software. Three (3) themes have been identified from the analysis which include: (i) refusal factor, (ii) attraction factor, and (iii) career counselling service improvement at public universities. Ten subthemes that emerged from the themes were: ethics, counsellor’s knowledge level, counsellor’s experiences, types of mentoring, locations of counselling and career units, student’s ignorance, intensifying counselling and career activities and increasing promotions. To conclude, counsellor’s personality, knowledge, and skills influence the utilisation pattern of career counselling services and counsellors are advised to continually improve their knowledge and skills in line with the client’s needs.